Genetic diversity and population structure of Toona ciliata revealed by simple sequence repeat markers. Issue 1 (1st January 2019) - Zhan, Xin; Li, Pei; Hui, Wenkai; Deng, Yanwen; Gan, Siming; Sun, Ye; Zhao, Xianhai; Chen, Xiaoyang; Deng, Xiaomei
Abstract: Toona ciliata (Meliaceae) is a rare, fast-growing commercial tree species that produces red timber with beautiful grains. It used to be widely distributed in the past, but few natural forests exist in the field now. Here, we tested 12 nuclear microsatellite markers derived from 551 individuals of 29 populations in China, and investigated the genetic diversity and population structure in T. ciliata . Our results revealed 146 alleles obtained from all of the populations studied here, with an average polymorphic information content of 0.723. The populations could be divided into two major genetic lineages using STRUTURE analysis: 14 and 15 populations from different provinces clustered in Western and Eastern genetic lineages, respectively. The genetic differentiation among the two genetic lineages was 28%. The genetic diversity of the Western lineage was higher than that of the Eastern lineage. Moreover, a Mantel test of the relationship between genetic and geographic distances revealed significantly positive correlations both among all 29 populations and within the Eastern genetic lineage, whereas there was no significant correlation in the Western genetic lineage. Therefore, in the conservation strategy of T. ciliatare sources, the two genetic lineages should be treated independently. To the best of our knowledge, these data are the first detailed characterization of the genetic structure and diversity of T. ciliata populations using nuclear microsatellite markers. The obtained results lay the foundation for preservation of the T. ciliata germplasm resources and support further artificial breeding efforts.